A Work study on rumstyle shoe factory - Bajar, Jean Corinna H.; Limcaoco, Katrina K.; Santos, Jovito U.; Tan, Patricia Ann C.; Valencia, Felicidad A.L (College of Engineering, 1989)
We have conducted a work study on RUMSTYLE SHOES, in fulfillment of a requirement in a course of methods engineering. This study serves as an application of the various techniques we have learned. A summary of the results are as follows : For the completion of the assembly of shoes, they undergo the following major operations : Pattern-making : includes the transfer of the design to the shoe material and the lining. The size is written on the material and it is bundled after an order slip is finished. Preparation of shoe material : this includes the cutting of the finished pattern. The shoe material and lining which were cut then glued together and sewn. Numbering : the shoe materials are numbered as to their size and stock no. by the owners. The owners also prepare the job tickets which will give the assignments to the different shoemakers. This is done inside the owner's house. Requisition of materials : upon issuance of the job tickets, the materials needed (counterboard and stiffener) are provided to the respective shoemakers. Shoe molding : the shoemakers gather the required number and size of the shoe lasts as indicated in their job tickets. Afterwhich they attach the counterboard and shoe material to these lasts. These are then brought to the oven for approximately two hours of drying. Afterwards, the nails used to temporarily attach the shoe material, are removed, and rugby is instead applied for final attachment. Sole attaching : the sole attacher then brings the shoe lasts (with the molded shoe materials) to the grinder and the sole portion of these lasts are smoothened. The soles are now attached using rugby. Heel attaching : with the indicated sizes of heels, the heel attacher gathers the heels, prepares them (puts rugby) and attaches them to the shoe lasts. Allowances on the soles are trimmed and the rubber soles are finally nailed on the heels. They next remove the shoe last and the heels are nailed from inside the shoes. Finishing : excess lining is trimmed and foam is placed on the counterboard. The shoes are cleaned with kerosene to soften the rugby, and the rugby is removed using the 'balibol'. The 'plantilla' is then placed with rugby. The edges of the heels are painted and the shoes are polished. The 'finishing' workers then make the boxes and the finished shoes are placed inside these. Labelling of boxes : this includes the numbering of the boxes, with corresponding labels (size and stock no.) and the inspection, which is done by the owners. Total time of operations : the computed total time of operations is approximately 28,983.10 seconds per pair or 8 hours, 3 minutes and 4 seconds for a pair of shoes. After covering the overall problem areas, we have arrived with the following, as our recommendations : Layout : restricted with the fact that long-term renovations on the layout would entail financial disadvantages on the part of the owners, a number of rearrangements would be the best alternative. To better document this proposal, we have sketched the recommended layout. The shoemakers (shoe molding workers) are brought near the dryer, the inventory room, and the shoe lasts' bin (as will be discussed later) since they avail of these the most. The succeeding stations are arranged according to the flow of the process (shoe molding, sole attaching, heel attaching and finishing). The remaining space is provided for back-order and finished goods' storage. This would cut down long transports between stations and machines. To replace the baskets containing the shoe lasts, a long rectangular bin, 13.5 ft. long x 2 ft. wide x 3 ft. tall, having shoe lasts of sizes 5', 5.5', 6', 6.5', 7', 7.5', 8', 9', and 10', and labelled accordingly. This would prevent the misplacement of the shoe lasts and the space occupied will be minimized. Material handling : to improve material handling (shoe lasts), shelves are recommended to be of standard dimensions : 3 ft. long x 1 ft. wide x 4 ft. tall, comprising three layers and wheels are to be attached. Such a "trolley shelf" would increase the efficiency of transporting these heavy shoe lasts, and unnecessary effort is minimized. This standardized dimension would also minimize the space occupied by the shelves at the same time that its full capacity is used. Another suggestion regarding the handling and transport of the finished shoes (in boxes), is a trolley. This would increase efficiency in the transfer of these finished goods to the storage section. As for the handling and application of rugby to the different parts, it is recommended that a toothbrush be used, (as already being done by one of the workers) or any other kind of applicator, instead of using bare fingers. This would eliminate unnecessary time and effort expended removing the rugby form from the fingers. Ventilation / air circulation : to improve working conditions, we recommend the implementation of electric fans, and blowers. The electric fans (ordinary desk fans) may be placed above the shoe lasts' bin, and the blowers, at the opposite wall. In addition to this, the grinding room may also have a window. These would make the workers feel a little more comfortable, and their endurance may be lengthened due to proper air circulation and ventilation. Lighting : The present lighting system will not be replaced, instead, an addition of a general lighting system would be an improvement. Since this would eliminate the glaring effects of the 'individual lights' thus, minimizing eye strain. Cleanliness/orderliness : painting the sides of the passageway would enhance order in the shop. This would serve as a 'boundary' for the passageway. Objects found within these painted lines, must immediately be removed, so as to facilitate a smoother passage of materials, workers, and transportation equipments. Each worker must be provided a trash can, and a box to contain all his neceesary tools. This would eliminate the time spent looking for the materials and tools needed during operations. Total time of operations : to minimize the total time of operations, it is recommended that a continuous supply of completely processed materials and parts be available. Transferring the work of grinding and finishing of various parts (e.g. heels, counterboard) from the 'main workers' to the 'inventory workers', would further smoothen the flow of processes. The main operations would now consist of the mere assembly of these completely processed materials and parts thereby lessening the assembler's effort and time. Better quality may also result due to concentration to assembly work alone. These changes have eliminated a total of 15 minor operations, 16 transports, 23 delays and 18 holds in the Two Handed Process Charts. The above recommendations are based on the succeeding discussions and documentations of recorded facts. Due to a limited knowledge of the actual restrictions, these are subject to the final analysis and decision of the owners.